Multiple cerebral cavernous hemangiomas masquerading as hemorrhagic brain metastases - Parissa Feizi, M.D.; Dhairya A. Lakhani, M.D.; Saurabh Kataria, M.D.; Samiksha Srivastava, M.D.; Abdul R. Tarabishy, M.D.; Gerard Deib, M.D.; Shitiz Sriwastava, M.D. (Radiology Case Reports, 2020)
Intracranial hemorrhagic metastases are a relatively common finding in patients with thyroid carcinoma. Consequently, more unusual vascular lesions may be overlooked in contemplating a differential diagnosis in this patient group. A 50-year-old female with previously treated papillary thyroid carcinoma presented to the emergency department following new onset seizures. Her work up revealed multiple intraparenchymal brain lesions, hyperdense on computed tomography and demonstrating susceptibility effect, T1 shortening and contrast enhancement on magnetic resonance imaging, suggestive of metastases. Subsequent studies revealed lesional architecture consistent with multiple cavernous malformations, made evident by resolution of edema and evolution of blood products. Clinicians should be aware of the possibility of unusual intracranial hemorrhagic lesions in oncology patients which may only become evident on serial imaging evaluation. Cavernous hemangioma has typical MRI characteristic features which includes “mulberry” appearance on T2-weighted and fluid attenuation inversion recovery images with varying internal signal intensity which indicates multiple stages of blood products within the cavernous hemangioma. The lesions commonly have a typical T2-weighted dark hemosiderin rim. Blood sensitive demonstrates prominent surrounding hypointensity representing blooming secondary to internal blood products and/or calcification, if present. Cavernous hemangioma may rarely demonstrate some degree of contrast enhancement. Perfusion imaging may show alteration in capillary permeability involving cavernous malformations which has been previously described in the literature.